High glutamate concentration reverses the inhibitory effect of microglial adenosine 2A receptor on NLRP3 inflammasome assembly and activation. (19th January 2022) - Du, Hao; Tan, Yan; Li, Chang-Hong; Zhao, Yan; Li, Ping; Ning, Ya-Lei; Gao, Ruo-Bing; Wang, Bo; Peng, Yan; Tan, Si-Wei; Huang, Zhi-Zhong; Chen, Xing; et al.
Highlights: Microglial adenosine 2A receptor regulates NLRP3 inflammasome assembly. Glutamate concentration modulates the effects of A2AR on NLRP3 inflammasome. A2AR regulates NLRP3 inflammasome at posttranscriptional level. Abstract: NLRP3 inflammasome plays a crucial role in the innate immune system. Our group previously reported that the microglial adenosine 2A receptor (A2A R) regulates canonical neuroinflammation, which is affected by the glutamate concentration. However, the regulatory effect of A2A R on NLRP3 inflammasome and the effects of glutamate concentration remain unknown. Therefore, we aimed to investigate the regulatory effect of microglial A2A R on NLRP3 inflammasome assembly and activation as well as the effects of glutamate concentration on the inflammasome assembly and activation. Experiments were conducted on magnetically sorted primary microglia from P14 mice. The results showed that pharmacological A2A R activation ameliorated NLRP3 activation under no or low glutamate concentrations, but this effect was reversed by high glutamate concentrations. Moreover, the mRNA levels of NLRP3 inflammasome-related genes were not affected by A2A R activation or the glutamate concentration. We further demonstrated that A2A R activation inhibited the interaction between NLRP3 and caspase 1 under no or low glutamate concentrations while promoting their interaction under high glutamate concentrations. The oligomerization of ASC also showed a similar trend. In conclusion, our findings proved that the high glutamate concentration could reverse the inhibition of A2A R on NLRP3 inflammasome activation by modulating its assembly, which provides new insights into the regulatory effect of A2A R on neuroinflammation under different pathological conditions.